ON THE CLASS OF ARRAY-BASED APM-LDPC CODES - A. Nassaj; A. R. Naghipour (Journal of Algebraic Systems, 2021)
We construct an explicit class of affine permutation matrix low-density parity-check (APM-LDPC) codes based on the array parity-check matrix by using two affine maps f (x) = x-1 and g(x) = 2x-1 on Z_m, where m is an odd prime number, with girth 6 and flexible row (column)-weights. Simulation results justify well performance, minimum-distances and cycle distribution of these codes in comparison the array-LDPC , structured QC-LDPC and APM-LDPC.